2020
DOI: 10.1177/0046958020957114
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Status and Self-Efficacy of Nurses During COVID-19 Outbreak: A Cross-Sectional Survey

Abstract: A novel coronavirus pneumonia broke out and gradually developed into a global public health problem. Health care workers, especially nurses, suffered from great occupational pressure and psychological distress during the outbreak of infectious diseases. We performed a cross-sectional survey to investigate the psychological status and self-efficacy of nurses in public hospital during COVID-19 outbreak between 16th and 25th February 2020. A total of 223 nurses participated in this study. The prevalence of anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
106
2
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(137 citation statements)
references
References 32 publications
12
106
2
17
Order By: Relevance
“…This could be due to longer work shifts and excessive workload as the outbreak forced high turnover rate of admission and presentation in the hospitals. As compared to the present study, the prevalence of anxiety symptoms was 38%–50%[ 21 22 23 ] and stress was up to 75%,[ 21 22 24 ] which is much higher. These studies having been done during the initial phases of the pandemic when the situations faced by the participants were more alarming and challenging in nature, might be the reason for this inconsistency from the present study.…”
Section: Discussioncontrasting
confidence: 78%
“…This could be due to longer work shifts and excessive workload as the outbreak forced high turnover rate of admission and presentation in the hospitals. As compared to the present study, the prevalence of anxiety symptoms was 38%–50%[ 21 22 23 ] and stress was up to 75%,[ 21 22 24 ] which is much higher. These studies having been done during the initial phases of the pandemic when the situations faced by the participants were more alarming and challenging in nature, might be the reason for this inconsistency from the present study.…”
Section: Discussioncontrasting
confidence: 78%
“…The prevalence of anxiety was 9.2% among nurses in this study. These findings paint a more favorable and rosier picture compared to earlier studies conducted during the early periods of the outbreak, which have reported a higher prevalence of anxiety (40.8%) among Chinese nurses [28]. Likewise, the findings on psychological distress were surprisingly high (>70%) in another work conducted during the initial stage of the outbreak [12].…”
Section: Discussionsupporting
confidence: 50%
“…The overall pooled point estimates of depression reported by the 62 studies [ 19 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , 34 , 35 , 37 , 39 , 42 , 43 , 45 , 48 , 49 , 51 , [53] , [54] , [55] , [56] , [57] , 62 , [64] , [65] , [66] , [67] , [71] , [72] , [73] , [74] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , 90 , 91 , [94] , [95] , [96] , [99] , [100] , [101] , [102] , [103] , [105] , [106] , [107] , [108] ] varied between 9% and 89% ( Fig. 4 : forest plots).…”
Section: Resultsmentioning
confidence: 99%